2021
DOI: 10.1021/acsbiomaterials.1c01175
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Erythrocyte Gel Loaded with Bulleyaconitine A for the Treatment of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease with clinical manifestations including joint cartilage, synovitis, and bone damage. Here we developed an injectable erythrocyte gel loaded with Bulleyaconitine A (BLA) for the treatment of RA and demonstrated its anti-inflammatory effects in vivo and in vitro. In vitro experiments showed that BLA could effectively down-regulate the expression of pro-inflammatory factor in activated macrophages through the nuclear factor-κB (NF-κB) pathway. In vivo expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Wang et al reported that homologous erythrocytes could form the hydrogel when they were subcutaneously injected. [149] In this system, blood clot was gel-like fibrin network trapping mass of erythrocytes, which was formed by coagulation cascade process of ex vivo blood. [150] Based on deep reddish color, the fabricated gels presented photothermal conversion under irradiation of NIR laser.…”
Section: Cellular Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported that homologous erythrocytes could form the hydrogel when they were subcutaneously injected. [149] In this system, blood clot was gel-like fibrin network trapping mass of erythrocytes, which was formed by coagulation cascade process of ex vivo blood. [150] Based on deep reddish color, the fabricated gels presented photothermal conversion under irradiation of NIR laser.…”
Section: Cellular Therapeuticsmentioning
confidence: 99%
“…[151] Except for the role of drug delivery, they could recruit lots of immune cells, including B cells, macrophage, and T cells. [150] Upon implantation, erythrocyte-based gels have showed curative effective to treat rheumatoid arthritis, [149] enhance bone repair, [151] and for cancer immunotherapy and cancer vaccination. [150,152]…”
Section: Cellular Therapeuticsmentioning
confidence: 99%
“…The diterpenoid alkaloid Bulleyaconitine A (BLA) is an active ingredient of Aconitum bulleyanum plant that has been approved for the treatment of chronic pain and rheumatoid arthritis in China [ 45 ]. The effects of BLA can be explained by its action on neuronal VGSCs.…”
Section: Natural Compounds With Effects On Voltage-gated Sodium Chann...mentioning
confidence: 99%
“…In addition, it is also used for local anesthesia ( Chan et al, 2021 ), analgesia ( Wang et al, 2008 ), anti-inflammation ( Zheng et al, 2017 ), and sweating ( Wu et al, 2021 ; Zhang et al, 2021 ). Aconitine has shown excellent efficacy in anti-inflammation, for instance, in the treatment of rheumatoid arthritis, by regulating IL-6 and TNF-α cytokine levels and inhibiting the activation of NF-κB signaling pathway ( Chen et al, 2021 ). Currently, several animal and cellular experiments have confirmed the inhibitory effect of aconitine alkaloids on malignant tumors ( Yao et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%